Preferences for Life-Prolonging Medical Treatments and Deference to the Will of God - Winter, Laraine (Journal of religion and health, 2009)
We defined and measured a dimension of religiosity frequently invoked in end-of-life (EOL) researchdeference to God's Will (GW)and examined its relationship to preferences for life-prolonging treatments. In a 35-min telephone interview, 304 older men and women (60 +) were administered the 5-item GW scale, sociodemographic questions, three attitude items regarding length of life, and measures of two health indices, depression, and life-prolonging treatment preferences. The GW scale demonstrated internal consistency (Cronbach's alpha = .94) and predictive and discriminant validity. Higher scores indicative of greater deference to GW were associated with stronger life-prolonging treatment preferences in poor-prognosis scenarios. Implications for the role of religiosity in medical decision-making are discussed.